Réponses

  • Utilisateur Brainly
2012-04-30T13:54:46+02:00

I=(3x²+7)+6x-1-(15x²+7x-3)=

3x^2+7+6x-1-15x^2-7x+3=-12x^2-x+9

x=1

(3x²+7)+6x-1-(15x²+7x-3I=10+6-1-(15+7-3)=-4

et -12x^2-x+9=-12-1+9=-4

 

J=x²-(3x²-15x+4)+(15x²-12x²-x)=x^2-3x^2+15x-4+15x^2-12x^2-x=x^2+14x-4

x=1

x²-(3x²-15x+4)+(15x²-12x²-x)=1-(3-15+4)+(15-12-1)=1-(-8)+2=11

x^2+14x-4=1+14-4=11

2012-04-30T14:19:01+02:00

I = 3x²+ 6x + 6 - 15x² - 7x + 3

I = -12x² - x + 9

 

J = x² + 3x² + 15x - 4 + 15x² - 12x² - x

J = 4x² + 15x - 4 + 3x² - x

J = 7x² + 14x - 4

 je souhaite t'avoir un peu aidée